Tuning of Load Frequency PID Controller of Electric Power System using Metaheuristic Algorithms - E, Pasala Gopi Research Scholar, E E; E, Dr. P. Linga Reddy Professor, E E (Iraqi Journal for Electrical and Electronic Engineering, 2016)
This paper investigates Load Frequency Control of multi area inter connected power system having different turbines with PID controller. The gain values of controller are optimized using different Metaheuristic Algorithms. The performance and validity of designed controllers were checked on multi area interconnected power system with various Step Load Perturbations. Finally, the performance of proposed controllers was compared with conventional controller and from the result it was proved that the proposed controller exhibits superior performance than conventional controller for various Step Load Perturbations.